The Practice of Traditional Game “Galah Kepong” to Develop Bodily-Kinesthetic and Interpersonal Intelligence Among Students - Maulina, Iin (Education, Science, and Technology International Conference, 2025)
Traditional games can serve as meaningful educational tools, particularly in teacher education programs where the development of physical and social-emotional competencies is essential. This study aims to explore the implementation of the traditional Indonesian game Galah Kepong and its contribution to the development of bodily-kinesthetic and interpersonal intelligences among early childhood teacher education students. Using a descriptive qualitative approach, the research involved 17 second-year students who participated in three structured game-based learning sessions. Data were collected through observation, interviews, and documentation. The study revealed that Galah Kepong supported improvements in bodily-kinesthetic intelligence, including coordination, balance, agility, and spatial awareness. In parallel, it also enhanced interpersonal intelligence through teamwork, communication, empathy, and emotional regulation. Reflection sessions after gameplay allowed students to articulate their learning experiences and connect them to their future teaching roles, particularly in promoting play-based, inclusive, and culturally responsive practices in early childhood education. Additionally, the study identified practical challenges in implementing traditional games within higher education, such as space limitations and varying levels of familiarity with the game. Overall, Galah Kepong proved to be an effective, joyful, and culturally grounded strategy to foster holistic competencies in prospective early childhood educators.